Gender, Income, And Religiosity In E-Commerce Payment Preferences - Arif, Muhammad; Rangkuti, Selvi Harisma (Journal of Islamic Financial Technology, 2025)
This study examines the influence of gender, income, and religiosity on payment method preferences in e-commerce transactions. Payment methods affect consumer convenience and purchasing decisions, but individual factors such as gender, income, and religiosity also play an important role. This research uses a quantitative approach with the SEM-PLS (Structural Equation Model-Partial Least Square) method. The research sample consisted of 54 respondents of the State Civil Apparatus (ASN) in Padangsidimpuan City, which was selected using the Cluster Sampling technique. Data were collected through questionnaires and documentation. The results showed that gender had a significant effect on payment method preferences (coefficient 0.517, p-value 0.041), while income had no significant effect (coefficient -0.217, p-value 0.170). Religiosity has a significant effect with coefficient -0.289 and p-value 0.028, indicating that a high level of religiosity tends to reduce preferences for payment methods that are not in accordance with sharia principles. Keywords: Gender, Income, Religiosity, Payment Method